Holistic Education Model: A key for child development - Shahid Khan, Zakia Shahid, Aswati Binti Hamzah, (Opción, 2020)
This conceptual paper aim to develop newly generation with the innovate designs. This study offered Holistic Educational Model (HEM) with the Islamic perspective. It suggests that the ultimate components of child psyche development that lead to well and superior performance in a society. The main objective of this study is to investigate the western and Islamic literature to design the proposed model. This study also investigates that how proposed model can reduce negative behavior of children. The literature revealed that children behavior and development is the main indication for the society. It shows that child development is the important factor for present society.